Hydrogen - fuel future - Biernat, Krzysztof; Samson-Bręk, Izabela Agata (Studia Ecologiae et Bioethicae, 2008)
Hydrogen it one of most spread radical on earth, this gas has to become alternative due to so general occurrence for mineral fuels exactly chance. Low is unchallenged advantage of employment of hydrogen in car engines emission, then hydrogen is fuel ecological completely. On way to general employment of hydrogen biggest barrier stagnant as storage of this gas is fuel and high cost of its production.